73.18.13 problem 27.1 (m)

Internal problem ID [15597]
Book : Ordinary Differential Equations. An introduction to the fundamentals. Kenneth B. Howell. second edition. CRC Press. FL, USA. 2020
Section : Chapter 27. Differentiation and the Laplace transform. Additional Exercises. page 496
Problem number : 27.1 (m)
Date solved : Tuesday, January 28, 2025 at 08:02:59 AM
CAS classification : [[_3rd_order, _with_linear_symmetries]]

\begin{align*} y^{\prime \prime \prime }-27 y&={\mathrm e}^{-3 t} \end{align*}

Using Laplace method With initial conditions

\begin{align*} y \left (0\right )&=2\\ y^{\prime }\left (0\right )&=3\\ y^{\prime \prime }\left (0\right )&=4 \end{align*}

Solution by Maple

Time used: 11.371 (sec). Leaf size: 46

dsolve([diff(y(t),t$3)-27*y(t)=exp(-3*t),y(0) = 2, D(y)(0) = 3, (D@@2)(y)(0) = 4],y(t), singsol=all)
 
\[ y = \frac {14 \sqrt {3}\, {\mathrm e}^{-\frac {3 t}{2}} \sin \left (\frac {3 \sqrt {3}\, t}{2}\right )}{81}+\frac {70 \,{\mathrm e}^{-\frac {3 t}{2}} \cos \left (\frac {3 \sqrt {3}\, t}{2}\right )}{81}+\frac {92 \cosh \left (3 t \right )}{81}+\frac {95 \sinh \left (3 t \right )}{81} \]

Solution by Mathematica

Time used: 0.363 (sec). Leaf size: 376

DSolve[{D[ y[t],{t,3}]-27*y[t]==Exp[-3*t],{y[0]==2,Derivative[1][y][0] ==3,Derivative[2][y][0] ==4}},y[t],t,IncludeSingularSolutions -> True]
 
\[ y(t)\to \frac {1}{162} e^{-3 t} \left (-162 e^{3 t/2} \cos \left (\frac {3 \sqrt {3} t}{2}\right ) \int _1^0-\frac {e^{-\frac {3 K[1]}{2}} \left (\sqrt {3} \cos \left (\frac {3}{2} \sqrt {3} K[1]\right )-3 \sin \left (\frac {3}{2} \sqrt {3} K[1]\right )\right )}{27 \sqrt {3}}dK[1]+162 e^{3 t/2} \cos \left (\frac {3 \sqrt {3} t}{2}\right ) \int _1^t-\frac {e^{-\frac {3 K[1]}{2}} \left (\sqrt {3} \cos \left (\frac {3}{2} \sqrt {3} K[1]\right )-3 \sin \left (\frac {3}{2} \sqrt {3} K[1]\right )\right )}{27 \sqrt {3}}dK[1]-162 e^{3 t/2} \sin \left (\frac {3 \sqrt {3} t}{2}\right ) \int _1^0-\frac {e^{-\frac {3 K[2]}{2}} \left (3 \cos \left (\frac {3}{2} \sqrt {3} K[2]\right )+\sqrt {3} \sin \left (\frac {3}{2} \sqrt {3} K[2]\right )\right )}{27 \sqrt {3}}dK[2]+162 e^{3 t/2} \sin \left (\frac {3 \sqrt {3} t}{2}\right ) \int _1^t-\frac {e^{-\frac {3 K[2]}{2}} \left (3 \cos \left (\frac {3}{2} \sqrt {3} K[2]\right )+\sqrt {3} \sin \left (\frac {3}{2} \sqrt {3} K[2]\right )\right )}{27 \sqrt {3}}dK[2]+187 e^{6 t}+30 \sqrt {3} e^{3 t/2} \sin \left (\frac {3 \sqrt {3} t}{2}\right )+138 e^{3 t/2} \cos \left (\frac {3 \sqrt {3} t}{2}\right )-1\right ) \]